Brief exploration of short and mid-term timeout effects on basketball scoring according to situational variables - Sampaio, J.; Lago-Penas, C.; Gomez, M. A. (European Journal of Sport Science, 2013)
The aim of this study was to identify the effects of timeouts on Basketball teams' performance differences, as measured by points scored by the team that calls a timeout and points scored by the opponent team according to game location, the quality of the opponent and the game quarter. Sixty games were analysed using the play-by-play game-related statistics from the Asociación de Clubes de Baloncesto (ACB) League in Spain (2009-2010 season). For each timeout, the points scored in the previous and post 3, 5 and 10 ball possessions were registered for the teams that called the timeout and for the opponents (n=436 and n=427, n=322 and n=319, n=112 and n=110 for 3, 5 and 10 ball possessions, respectively). For the teams that called the timeout, the results reflected positive effects on points scored, with increases of 1.59, 2.10 and 2.29 points during the period within the third, fifth and tenth timeout ball possessions. For the teams that have not called the timeout, the results identified timeout negative effects in points scored, during the period within the third and fifth ball possessions (decreases in points scored of 1.59 and 1.77, respectively). Unexpectedly, the situational variables had little or no effects on points scored, which opens up this important topic for further studies and discussion.